(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: Neuromuscular electrical stimulation (NMES) is a relevant therapeutic strategy in the context of rehabilitation. Different NMES waveforms have been used to evoke contractions. Conventional NMES consists of pulsed currents (PC) with phase/pulse durations <500 µs delivered between 20 and 100 Hz. Another commonly used current in clinical practice is high frequency alternating current (KFAC) with frequencies ranging from 1 to 10 kHz, applied at a peak frequency between 1 Hz and 100 Hz and a peak duty cycle of 10% or more, proposed to reduce perceived discomfort during electrical stimulation. To date, few studies have evaluated submaximal and maximal evoked torque related to perceived discomfort with different NMES currents and phase durations. OBJETIVOS: To determine the influence of different electrical stimulation curr ents and phase durations on torque, efficiency, and discomfort. MÉTODOS: The study protocol was approved by the Institutional Review Board of the University of Brasília (protocol 67915523100008093) and reported alongside CONSORT guidelines (Registry NCT05894044). KFACs with frequencies of 1 kHz (Australian current) and 2.5 kHz (Russian current), along with pulsed currents (PC) with narrow phase durations (200 us) or wide phase durations (500 us), were randomly applied to the triceps surae muscle of healthy participants using a crossover design. The measured variables included intensity, evoked torque, efficiency, and discomfort under maximal and submaximal conditions during a neuromuscular electrical stimulation protocol. Statistical analyses were conducted using a two-way mixed-model ANOVA with repeated measures. Forty-four participants were included. RESULTADOS: No significant differences were observed in evoked torque or discomfort among the different currents or phase durations. Regarding current efficiency, no significant differences were found between high-frequency or medium-frequency currents; however, differences were observed concerning phase duration. Currents with longer phase durations demonstrated better efficiency, requiring lower intensity compared to currents with shorter phase durations. CONCLUSÕES: Currents with longer phase durations appear to be more efficient in generating torque, producing higher torque with lower current intensity. Future studies should test these currents in populations with musculoskeletal impairments, such as bedridden patients or those with muscle weakness. IMPLICAÇÕES: The findings of this study provide important insights into the benefits and possibilities of NMES, indicating greater safety for both patients and therapists when using this technique in clinical practice. Additionally, these results serve as a foundation for further studies involving specific populations, particularly when the goal is muscle strengthening through neuromuscular electrical stimulation.